Dhanyavaad India - Vijay Gupta Ed; GUPTA (Vijay) Ed (New Delhi: The High Commission of the Republic of South Africa in India, 1946)
A tribute to the heroes and heroines of India who supported the liberations struggle of South Africa
Keywords: South African Leaders in India; African National Congress; Indian Youth Congress